Lung Recruitment Strategies During High Frequency Oscillatory Ventilation in Preterm Lambs - Miedema, Martijn; McCall, Karen E.; Perkins, Elizabeth J.; Oakley, Regina B.; Pereira-Fantini, Prue M.; Rajapaksa, Anushi E.; Waldmann, Andreas D.; Tingay, David G.; van Kaam, Anton H. (Frontiers in Pediatrics, 2019)
Background: High frequency oscillatory ventilation (HFOV) is considered a lung protective ventilation mode in preterm infants only if lung volume is optimized. However, whilst a ‘high lung volume strategy’ is advocated for HFOV in preterm infants this strategy is not precisely defined. It is not known to what extent lung recruitment should be pursued to provide lung protection. In this study we aimed to determine the relationship between the magnitude of lung volume optimization and its effect on gas exchange and lung injury in preterm lambs. Methods: 36 surfactant-deficient 124-127 d lambs commenced HFOV immediately following a sustained inflation at birth and were allocated to either 1) no recruitment (low lung volume; LLV), 2) medium- (MLV) or 3) high lung volume (HLV) recruitment strategy. Gas exchange and lung volume changes over time were measured. Lung injury was analysed by post mortem pressure-volume curves, alveolar protein leakage, gene expression and histological injury score. Results: More animals in the LLV developed a pneumothorax compared to both recruitment groups. Gas exchange was superior in both recruitment groups compared to LLV. Total lung capacity tended to be lower in the LLV group. Other parameters of lung injury were not different. Conclusions: Lung recruitment during HFOV optimizes gas exchange but has only modest effects on lung injury in a preterm animal model. In the HLV group aiming at a more extensive lung recruitment gas exchange was better without affecting lung injury.